Pengaruh Latihan Keseimbangan Dinamis Terhadap Pola Jalan Pada Lansia Di Posyandu Gonilan - Manafiah, Anisatun, Maskun Pudjianto, S.Pd., M.Kes (2016)
Background: In the elderly there is a change associated with the phase pattern of road running, limited step, the running speed. Along with the changes that occur in anatomically and physiologically in the elderly, it would require an exercise to improve the strength in the lower limbs that support for the process of walking. One of the exercises that can be done is a dynamic balance training. Objective: To determine the effect of exercise on the pattern of the dynamic balance in elderly at centre for elderly health care and information Gonilan. Methods: This study is a quasi experimental with pre and post test with control group design with a number of samples is 52 samples. Measuring instrument used is the Dynamic Gait Index. Data were analyzed using paired samples t-test to test the influence and Mann-Whitney test to test different influences. Results: There is dynamic balance exercise influence on the pattern of the way the elderly are the results obtained 0,016 when walking on a flat surface, 0,018 onthe change in walking speed, 0,000 on walks with his head turned to the right or left, 0,001 on a walk with your head looking up, 0,016 on running and stopping, 0,050 on the walk around obstacles, in the treatmeant group. While the influence of different test results there is a significant change in walking speed 0,030, walking around obstacles 0,008, and move 0,002. Conclusion: Providing a dynamic balance training with a frequency of 2 times a week for 4 weeks was shown to significantly influence the way roads in elderly at centre for elderly health care and information Gonilan. Keywords: Exercise Dynamic Balance, Gait, Elderly.